Nano-Enhanced Tri-Organotin (IV) Complexes from a Ciprofloxacin Hybrid: Synthesis, Characterization, and Superior Antifungal Activity - Aliyaa Dhahir Mohsin; Angham G. Hadi; Rana A. K. Al-Refaia (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Organotin (IV) compounds are of significant interest in both the chemical and medicinal sectors. Among these, tri-organotin (IV) derivatives (R3SnX) stand out due to their potent biological activity and their distorted trigonal bipyramidal geometry. The present study details the synthesis, nano-formulation, and improved antifungal activity of three new tri-organotin (IV) complexes. These complexes have been synthesized from a hybrid ligand, formed from ciprofloxacin and 5-aminosalicylic acid, followed by modification of the carboxylate functional group with chloroacetic acid. These compounds have been completely characterized by FT-IR, multinuclear NMR spectroscopy (¹H, ¹³C, ¹¹⁹Sn), and CHNS analysis. To enhance their biological activity, the synthesized complexes have been nano-formulated with triangular silver nanoparticles (AgTNPs). The antifungal activity of both pure and nano-formulated complexes has been investigated against Fusarium spp. In vitro antifungal assays against Fusarium spp. revealed that the triphenyltin complex (T3) was the most active among the pure compounds, achieving a 20% inhibition rate at 2 mg/mL, attributed to its high lipophilicity and aromatic content. Remarkably, the nano-formulated version (AgTNPs-T3) demonstrated a significant synergistic effect, increasing the inhibition rate to 55% at the same concentration, a 2.75-fold enhancement compared to the unmodified complex. This superior performance is attributed to the high surface area-to-volume ratio and sharp vertices of the AgTNPs, which facilitate better membrane penetration and ROS generation.